2012
DOI: 10.1002/wcm.2252
|View full text |Cite
|
Sign up to set email alerts
|

Anonymous authentication protocol based on elliptic curve Diffie-Hellman for wireless access networks

Abstract: Anonymous channel tickets have been proposed as a way to provide user anonymity and to reduce the overhead of re‐authentication for authentication in wireless environments. Chen et al. proposed a secure and efficient protocol, based on a protocol proposed by Yang et al., which is resistant to guessing attacks on networks from which users’ secret keys are easy to obtain. However, their scheme is time‐consuming in the phases of ticket issuing and authentication. Furthermore, a malicious attacker can utilize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 26 publications
(30 reference statements)
0
22
0
Order By: Relevance
“…As reported in [31,32] the average execution time of a modular exponentiation, an elliptic curve point multiplication and a hash function operation is 522 ms, 63.075 ms, and 0.5 ms, respectively. Moreover, it is assumed that the time of performing an exclusive-or operation is negligible.…”
Section: Authentication Phasementioning
confidence: 96%
See 1 more Smart Citation
“…As reported in [31,32] the average execution time of a modular exponentiation, an elliptic curve point multiplication and a hash function operation is 522 ms, 63.075 ms, and 0.5 ms, respectively. Moreover, it is assumed that the time of performing an exclusive-or operation is negligible.…”
Section: Authentication Phasementioning
confidence: 96%
“…In order to provide a precise performance comparison, the experiment data reported in [31,32] are used. As reported in [31,32] the average execution time of a modular exponentiation, an elliptic curve point multiplication and a hash function operation is 522 ms, 63.075 ms, and 0.5 ms, respectively.…”
Section: Authentication Phasementioning
confidence: 99%
“…The Hsieh–Leu protocol consists of three phases: (i) registration; (ii) ticket issuing; and (iii) session key update. The notations used in this paper are presented in the succeeding texts.…”
Section: Review Of Hsieh–leu Protocolmentioning
confidence: 99%
“…After that, Youn et al showed that the protocol proposed in is not anonymous, and Mun et al showed that the protocol in achieves neither anonymity nor perfect forward secrecy , which is an important property in practice. In 2011, Chen et al proposed another efficient protocol secure against password guessing attack, but very recently, Hsieh and Leu showed that the protocol is vulnerable to denial of authentication attack, which is a special type of denial of service attack. Hsieh and Leu also proposed an improved scheme to overcome the weakness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation